Terapi Oral dan Tetes Mata Topikal pada Green Nail Syndrome - Putti Fatiharani Dewi; Ambar Aliwardani; Nugrohoaji Dharmawan (MEDICINUS, 2021)
Background: Green nail syndrome is one of the chromonychia caused by infection of Pseudomonas aeruginosa, characterized by onycholysis and greenish-black discoloration of the nail. There were no reports regarding the incidence of green nail syndrome in Indonesia. Predisposing factors for the occurrence of green nail syndrome include onychomycosis, high activity in moist and wet conditions, diabetes mellitus, and immunosuppression. Case: A 51-year-old man complained about greenish-black discoloration on his fingernails. Dermatological examination in 1st and 3rd digit of the right hand, as well as 1st digit of the left hand, found multiple greenish-black discoloration with onychodystrophy. Dermoscopy examination of the affected nails showed greenish-black pigmentation in the distolateral nails with peripheral fading. Culture examination using MacConkey agar showed colonies of greenish-brown pigments. The patient was diagnosed with green nail syndrome and treated with ciprofloxacin 500 mg/day and topical polymixin B eye drops b.i.d. for 3 weeks, resulting in good outcome. Discussion: The diagnosis of green nail syndrome is made based on anamnesis, physical examination, and bacterial culture. showing a distinctive feature. The predisposition factor in this case, is the frequent washing hands habit of the patient up to more than ten times per day. Treatment using topical eye drops facilitates the absorption of active ingredients into the nails.